The relationship between social support and smartphone addiction among Chinese college students: the mediating role of loneliness and the moderating role of meaning in life - Liu, Jialei; Zhang, Yongli; Zhang, Yu; Wang, Qinglei (Frontiers in Public Health, 2025)
BackgroundSmartphone addiction has become a significant public health concern among Chinese college students, adversely affecting their academic performance, social interactions, and psychological well-being. Based on the social support buffering hypothesis and compensatory internet use theory, loneliness may mediate the relationship between social support and smartphone addiction, with meaning in life potentially moderating this process.MethodsA cross-sectional study design was employed. Valid data were collected from 2076 Chinese college students using the Social Support Rating Scale for College Students, the 8-item UCLA Loneliness Scale (ULS-8), the Meaning in Life Questionnaire, and the Smartphone Addiction Scale-Short Version. Data analysis was conducted using SPSS 27 and the PROCESS macro to examine the mediating effect and the moderated mediation effect.ResultsSocial support was significantly negatively correlated with smartphone addiction. Loneliness mediated this relationship, accounting for 64.71% of the total effect. Meaning in life significantly moderated the path from loneliness to smartphone addiction. Simple slope analysis indicated that the positive predictive effect of loneliness on smartphone addiction was stronger for individuals with high levels of meaning in life.ConclusionSocial support may reduce the risk of addiction by alleviating loneliness; however, higher levels of meaning in life may amplify, rather than weaken, the negative effect of loneliness. This study reveals the complex interplay between social and existential factors in addiction and suggests that future interventions should focus on enhancing social support.